OPTIMAL CHOICE OF DIAGNOSTIC TACTICS AND MINIMALLY INVASIVE SURGICAL TREATMENT OF LIVER ECHINOCOCCOSIS - Makhramkulov Z.M. (Research Focus International Scientific Journal, 2024)
Some of them are known to cause human echinococcosis, and there are reasonable doubts about others. Diagnosis is confirmed by epidemiological history, clinical presentation, radiological imaging, and serological tests. Various pathological forms can become life-threatening, and in these cases, treatment is extremely difficult. The main goal of treatment is the complete cure of the disease in order to avoid further complications and relapses. Liver surgery using various techniques gives the best results with acceptable morbidity and mortality rates. In Uzbekistan, this disease is endemic with high incidence and prevalence. The surgical department of the 1st clinic of the Samarkand State Medical Institute has extensive experience in the treatment of echinococcal liver disease. This article focuses on the epidemiology, etiopathogenesis, diagnosis and surgical treatment of liver echinococcosis.